학문 목적 한국어 학습자의 토론 능력 향상을 위한 끼어들기 교수의 효과 - 황선영 (언어와 문화, 2018)
The purpose of this study is to assess the effects of explicitly teaching interruption in Korean classes for academic purposes. Moreover the study goes on to suggest appropriate teaching methods of pragmatic items related to interruption. For this study, an adjusted PPP model was developed to teach level-six Korean learners with academic purpose about discourse markers of interruption, and appropriate tones for interrupting. As a result, the frequency of turn-taking and deliberate interruptions during debating discourses increased significantly. Furthermore, learners actively tried to take their turns using the interruption expressions taught, or strategically used raising tones to maintain the floor whereas turn-taking only occurred at the syntactic completion of current speaker’s utterance before the teaching. This shows that teaching methods originally developed for vocabulary or grammar can also be applied to pragmatic items. With the growing demand for teaching methods of pragmatic items, this study will serve as a specific example of a teaching method of pragmatic items and of testing its explicit effects.
Keywords: 순서 교대; 끼어들기; 교체 적정 지점; 토론; 학문 목적 한국어 학습자.화용적 항목; 교육적 개입; turn-taking; interruption; ransition relevance point; debate; Korean for academic purpose learners; pragmaric item; pedagogical intervention